Strategy for Strengthening the Beringin Village Community Through the Implementation of the Multidimensional KKN Program - Sakinah, Gita; Hafizh, Muhammad Abdul; Hutauruk, Sayyidah Marwa; Afriani, Widya; Widya, Syipa Arista; Sriani, Sriani (Civiliza Publishing, 2025)
he Community Service Program (KKN) is increasingly positioned as a strategic service-learning model for community empowerment and the achievement of the Sustainable Development Goals (SDGs) at the village level. Through a collaborative and sustainable approach, service-learning integrates education, community service, and measurable impacts across social, economic, environmental, and civic dimensions. This study describes the multidimensional implementation of KKN in Beringin Village, which included social education, economic empowerment (dishwashing soap training and the introduction of branding and marketing for MSMEs), environmental programs, strengthening religious moderation and youth engagement, as well as support for digital village data governance and activity documentation. A descriptive-participatory method was applied through observation, focus group discussions, demonstrations, and field documentation. Initial findings indicate improvements in literacy regarding bullying prevention in partner schools, enhanced basic entrepreneurial skills among household and MSME actors, and the adoption of environmentally friendly practices through biopore infiltration holes for organic waste management and water conservation. These findings are consistent with studies published in SINTA journals, which highlight the effectiveness of branding training and biopore adoption. From a governance perspective, the thematic KKN model serves as a platform for student–citizen collaboration and strengthening village networks. This article formulates a replication strategy involving village asset mapping, designing an integrated service-learning curriculum, applying simple and realistic impact measurements, and planning sustainability beyond the KKN period.